Choosing wisely: The impact of patient selection on efficacy and safety outcomes in the EINSTEIN-DVT/PE and AMPLIFY trials. Issue 149 (January 2017) - Beyer-Westendorf, Jan; Lensing, Anthonie W.A.; Arya, Roopen; Bounameaux, Henri; Cohen, Alexander T.; Wells, Philip S.; Middeldorp, Saskia; Verhamme, Peter; Hughes, Rodney; Kucher, Nils; Pap, Akos F.; Trajanovic, Mila; et al.
Abstract: Background: The results of the EINSTEIN-DVT/PE and AMPLIFY trials, which compared rivaroxaban and apixaban with conventional anticoagulation therapy for acute venous thromboembolism (VTE), respectively, are often compared. However, the trials differed in duration of therapy (3–12 and 6 months, respectively) and in patient selection (few exclusion criteria and more stringent exclusion criteria, respectively). Methods: To determine the effect of these methodological differences on outcomes, the patients enrolled in EINSTEIN-DVT/PE were divided into 2 cohorts; the 5253 patients that matched the exclusion criteria for AMPLIFY and were treated for at least 6 months (cohort 1) and the 2368 patients who would have been ineligible for AMPLIFY (cohort 2). Results: Compared with patients in cohort 2, those in cohort 1 were older and more often male and there were more with unprovoked VTE, prior VTE, cancer and known thrombophilia. In cohort 1, rivaroxaban would have significantly reduced recurrent VTE (relative risk [RR], 0.64; 95% confidence interval [CI], 0.43–0.95) and major bleeding (RR, 0.50; 95% CI, 0.30–0.82) compared with conventional therapy, whereas the two treatments would have had similar effects on recurrent VTE (RR, 1.08; 95% CI, 0.65–1.79) and major bleeding (RR, 1.03; 95% CI, 0.48–2.18) in cohort 2. Conclusions: This analysis illustrates the influence of patient selection and treatments duration on outcome results and highlights the limitations of cross-trial comparisons.